SOCIAL MEDIA AND COMMUNICATION ETHIC IN ISLAMIC PERSPECTIVE - Desi Erawati, Lisnawati (IAIN Tulungagung, 2019)
Social media is very useful for establishing warm communication between family, friends, and various society. For those, needed to keep a good communication relationship. This paper examines how communication ethics on social mediafor married couples to prevent family disharmony. Uses literature studies, this paper analyzes primary sources, namely positive law, interpretation, hadith, and references related to social media. Then it is also added with secondary data from magazines, newspapers, documentation from the local religious court. The results of the study indicate that there are seven communication ethics through social media: taking benefits and leaving losses, meaning that social media has benefits if used wisely; practice fair time management; be open with your partner; selecting friends wisely; say the corresponding statement in posts and comments; keep the couple’s disgrace and not indulge themselves on social media; and look after self-esteem.